PENGEMBANGAN PENDIDIKAN BISNIS DAN PEMAHAMAN HUKUM DI SKOW YAMBE KOTA JAYAPURA (DEVELOPMENT OF BUSINESS EDUCATION AND LEGAL UNDERSTANDING IN SKOW YAMBE, JAYAPURA CITY) - muhtar syam; Dani Arisandi DN (LPPM Universitas Muhammadiyah Papua, 2026)
Skow Yambe Village, located on the Indonesia-Papua New Guinea border, has significant economic potential, particularly in the micro-enterprise and cross-border trade sectors. However, limited business education and a low understanding of business law hinder the community's economic development. This community service activity aims to improve the community's capacity in business management and legal literacy related to business legality and protection. The method used is a participatory approach through observation, counseling, training, and mentoring. The materials provided include business plan development, simple financial management, marketing strategies, and an understanding of business legality and consumer protection. The results of the activity indicate an increase in participants' understanding of business management and awareness of the importance of business legality. The community has begun implementing simple financial records and demonstrated readiness to process business permits. This activity demonstrates that integrating business education and legal understanding is an effective strategy in promoting the empowerment and economic independence of border communities. Sustainability of the program through mentoring and multi-stakeholder collaboration is essential to ensure long-term impact.